INNV-21. IN NEWLY-DIAGNOSED GLIOBLASTOMA, FRAILTY/SARCOPENIA PREDICTS 30D MORBIDITY & 30D, 90D, AND OVERALL MORTALITY AS ACCURATELY AS CURRENT STANDARDS. (11th November 2019) - Zakaria, Hesham; Chandra, Ankush; Macki, Mohamed; Robin, Adam; Walbert, Tobias; Chang, Victor; Kalkanis, Steven; Lee, Ian
Abstract: INTRODUCTION: Identification of novel prognostic biomarkers for glioblastoma (GBM) could stratify patients between aggressive or palliative treatments. Frailty, as measured by sarcopenia (lack of muscle mass), has been proven to predict survival in cancers. We evaluate whether the frailty/sarcopenia phenotype (FSP) predicts morbidity and mortality in GBM, and compare it to other survival markers. METHODS: In 257 patients undergoing initial diagnostic surgery for GBM, FSP was defined by temporalis muscle thickness from preoperative MRI; patients were grouped into tertiles (thirds) based on size, which corresponded to the severity of FSP. Morbidity and mortality hazard ratios were calculated from surgery using multivariate analysis, accounting for age, gender, past medical history, tumor focality / laterality / eloquence / volume, extent of resection, MGMT / IDH status, and initiation of postoperative chemo/radiation. Morbidity was defined as any of these events within 30d: DVT, PE, SSI, UTI, MI, urinary retention, ileus, readmission. RESULTS: FSP at diagnostic surgery predicted any morbidity (OR2.98, P = 0.005) at 30d. FSP at diagnostic surgery was the only risk factor associated with 30d mortality (OR10.0, P = 0.030), and was also strongly associated with 90d mortality (OR25.0, P = 0.003). FSP at diagnostic surgery was associated with decreased overall survival (OR0.41, P < 0.001) at a level comparable to other mortality predictors, including temozolomide/EBRT (OR0.27), gross total resection (OR0.54), favorable MGMT (OR0.44) or IDH (OR0.44) mutations. Kaplan-Meier curves display overall survival based on severity of FSP. CONCLUSION: FSP is a preoperative, simple, accurate, and non-invasive methodology to predict 30d morbidity & 30-day, 90-day, and overall mortality from diagnosis in GBM. FSP is independent of age (not an age surrogate), demographic, oncologic, genetic, surgical, and therapeutic factors. Mortality prediction is comparable to temozolamid/EBRT, total resection, MGMT, and IDH. It is a low cost, intuitive, and potentially universal methodology to guide treatment decision making.